A Biomimetic Heteroditopic Receptor for Zwitterions in Protic Media. Issue 2 (13th November 2014) - Cornut, Damien; Moerkerke, Steven; Wouters, Johan; Bruylants, Gilles; Jabin, Ivan
Abstract The efficient synthesis of calix[6]cryptothiourea 6 was achieved through a two‐step sequence that involves a key [1+1] macrocyclization step. It was shown by NMR spectroscopy that this heteroditopic receptor can bind zwitterions in protic media with an outstanding selectivity for β‐alanine betaine G5, which is likely due to a high complementarity between the two partners. This result constitutes a rare example of cavity complexation of a zwitterion by a calix[6]arene. In comparison with the parent urea‐based receptors, 6 behaves as a much more efficient host for betaines. This strengthening of the binding properties is due to the better preorganization of the tripodal hydrogen‐bonding cap as well as to the higher acidity of the thiourea groups and their poor ability to self‐associate. Remarkably, host 6 is able to perform solid–liquid as well as liquid–liquid extraction of G5. Finally, 6 provides an excellent structural model for the binding site of glycine betaine G4 encountered in natural systems.